Translations of Non-Russian Soviet Literature in the Estonian Book Production (1940s-1980s) - Möldre, Aile (Knygotyra, 2020)
This paper explores the dynamics of publishing of non-Russian Soviet literatures in Soviet Estonia, establishing the output of titles and the most popular source literatures. The analysis follows the position of Soviet national literatures during four periods in political history: the Stalinist years, the Thaw, Stagnation, and Perestroika. The study uses statistical yearbooks, bibliographies, archival material, as well as research literature as sources. The publishing of Soviet literature was strongly regulated by the publishing authorities and dependent on ideological directions. The analysis demonstrates that the proportion of the non-Russian Soviet literatures started to increase during the Thaw period, but the peak of its production was reached during the 1970s and the beginning of the 1980s due to official pressure. The total number of source literatures was 49, demonstrating the diversity of translation production, although they were represented equally. The top source literatures were Latvian, Lithuanian, and Ukrainian. The interest of the literary circles and reading audiences in the translations was rather weak, although the top authors attracted the attention of the more intellectual segment of readers.
Keywords: publishing; translations; Estonia; Soviet era; Soviet national literatures